Insidensi Fibrosis Paru Beserta Faktor-Faktor Risikonya pada Pasien Post COVID-19 di RSUD Al-Ihsan Bandung Tahun 2020-2021 - Danty Rahmanita; R.A Retno Ekowati; Widhy Yudistira Nalapraya (UNISBA Press, 2022)
Abstract. Introduction: Coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which was first discovered in Wuhan, China at the end of December 2019. Fibrosis occurs as a consequence of wound healing, due to pulmonary epithelial injury. The occurrence of pulmonary fibrosis in post-COVID-19 patients is associated with certain risk factors. Methods: this study is an observational analytic study using a cross sectional approach. This research used secondary data of post COVID-19 patients at Al- Ihsan Hospital in Bandung with total sampling method of 30 patients in the 2020- 2021 period. Results : The results of this study showed that there is a picture of the lung fibrosis of post-Covid 19 patients at Al-Ihsan Hospital Bandung in 2020-2021, as many as 86.7%. Conclusion : Factors associated with pulmonary fibrosis such as gender, advanced age, smoking, alcoholism, diabetes, hypertension and coronary artery disease. The result was p - value (p> 0.05) for all risk factors associated with pulmonary fibrosis, so it can be concluded that there is no relationship between risk factors associated with pulmonary fibrosis formation in patients of post-COVID-19 patients at Al-Ihsan Hospital Bandung. Abstrak. Pendahuluan: Coronavirus disease 2019 (COVID-19) merupakan salah satu penyakit infeksi menular akut yang disebabkan oleh severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) yang pertama kali ditemukan di Wuhan, China pada akhir Desember 2019. Fibrosis terjadi sebagai konsekuensi terhadap penyembuhan luka akibat terbentuknya cedera epitel paru. Terjadinya fibrosis paru pada pasien post COVID-19 berkaitan dengan faktor-faktor risiko tertentu. Metode : Penelitian ini merupakan penelitian dengan desain analitik observational melalui pendekatan cross sectional. Pengambilan sampel menggunakan data sekunder pasien post COVID-19 di RSUD Al-Ihsan Bandung dengan metode total sampling sebanyak 30 pasien pada periode 2020–2021. Hasil : Berdasarkan hasil penelitian, terdapat gambaran fibrosis paru pasien post Covid 19 di RSUD Al- Ihsan Bandung Tahun 2021 sebanyak 86,7%. Simpulan: Faktor-faktor yang berhubungan dengan fibrosis paru seperti jenis kelamin, usia lanjut, perokok, alcoholism, diabetes, hipertensi dan penyakit arteri koroner diperoleh p – value (p>0,05), sehingga dapat disimpulkan tidak terdapat hubungan antara faktor-faktor risiko yang diteliti terhadap terbentuknya fibrosis post COVID-19 pada pasien post COVID-19 di RSUD Al- Ihsan Bandung.